Remediation of acetochlor-contaminated maize field soil using Serratia odorifera AC-1 fertilizer: effects on soil microbial communities - Zhang, Zhengyi; Shi, Zhenting; Zheng, Lining; Zhang, Hao (Frontiers in Microbiology, 2025)
Acetochlor is a chloroacetamide herbicide that is widely applied in corn fields. Nevertheless, the long-term usage of acetochlor in the soil leads to residues, which severely affect the germination of corn seeds and the growth of seedlings, and even exert an influence on the soil microbial community. Microbial degradation of acetochlor is the principal approach for restoring the soil microbial ecology. In this study, the Serratia odorifera AC-1 strain was isolated and identified from the soil for the degradation of residual acetochlor in the soil. To enhance the degradation efficiency, a solid microbial agent was prepared by using activated carbon as a carrier and the AC-1 strain at a 1:1 ratio and applied to the soil for degradation and remediation experiments. The content of the microbial cells in the solid microbial agent was 1.49 × 106 CFU/g after 120 days of preparation. The application of the AC-1 solid microbial agent significantly influenced the relative abundance of soil microbial communities (Actinobacteria, Firmicutes, and Proteobacteria), increasing the diversity of bacterial populations in the soil. The experimental results indicated that after the application of the AC-1 solid microbial agent, the plant height, stem diameter, and photosynthetic efficiency of corn seedlings under acetochlor stress were significantly elevated. When the application rate of the AC-1 solid microbial agent was 5.00 mg/kg, the stem diameter of corn increased by 56.4% compared with the control group. When the acetochlor concentration in the soil was 6.65 mg/kg, the DT50 value of the AC-1 solid microbial agent was 2.28 days. This study clarified the degradation mechanism and remediation capacity of the Serratia odorifera AC-1 strain in acetochlor-contaminated soil and proposed a new strategy to improve the stability and degradation efficiency of the microbial strain by optimizing the immobilization technology of the strain on activated carbon. This research provides a scientific basis and technical guidance for the future application of bioremediation technology in the field environment to remove pesticide residues, restore soil health, and enhance crop productivity.